Content and Language Integrated Learning in Writing in the Junior High School - Antari, Putu Dian Juni (Journal of Educational Study, 2023)
The purpose of this research is to analyze the steps and writing competency implemented through CLIL in writing. This research is aimed at seventh-grade students in the Junior High School at SMPN 4 Busungbiu, Singaraja. The participants of students in the Junior High School were 30 students in one class. The first time, the researcher found the diagnostic of students writing competency in SMPN 4 Busungbiu. The mixed method combining descriptive qualitative and quantitative was applied in this study. The data collected by Classroom research that determined by who does such as the teacher, the research then used a syntax, lesson plan (RPP), and rubric as the instruments. The result of students writing competency is seen by the writing component, namely: 1) Title, 2) Topic sentence, 3) Develop Topic Sentence, 4) Grammatical, 5) Vocabulary, and 6) Punctuation. There were 73.3% students had corrected in writing descriptive text based on seven components of writing. Almost same with descriptive text, there were 70% students had corrected in writing procedure text. The result showed a significant increase in students’ writing competency after being implemented CLIL method by the teacher.